Primary adenoid cystic carcinoma of the nasolacrimal duct treated with proton beam therapy. Issue 6 (December 2015) - Wada, Kota; Arai, Chiaki; Suda, Toshihito; Nagaoka, Masato; Shimura, Eiji; Yanagisawa, Sawako; Edamatsu, Hideo
Abstract Primary malignant tumors of the lacrimal passage, particularly of the nasolacrimal duct, are rare. We describe a 72-year-old woman who presented with lacrimation 5 years previously. She had pain and bloody and purulent lacrimation, and a mass was identified in the inferior meatus. Accordingly, she was diagnosed with primary adenoid cystic carcinoma of the nasolacrimal duct. She was treated with proton beam therapy and showed a favorable response. Owing to the long-term risks of recurrence and distant metastasis, adenoid cystic carcinoma requires sufficient follow-up.